Decoding cancer proteins: An in silico characterization of human TSPAN1 - Yap, Rianne Casey Yang (Animo Repository, 2023)
Human tetraspanin-1 (TSPAN1) originates from the protein group, transmembrane 4 superfamily (TM4SF), which are regarded as molecular scaffolds due to their ability to distribute proteins into varying functions such as microdomains encompassing adaptor, adhesion, and signaling proteins. These tetraspanin-enriched microdomains (TEMs) are formed through their interactions with transmembrane receptors and other proteins, allowing them to participate in essential biochemical processes occurring in the cellular environment. Given its significant presence in these activities, studies have found TSPAN1 to be abundantly associated with certain pathological conditions, such as the development of various types of cancers, including colorectal, esophageal, and prostate cancers. Despite the overexpression in cancer progression, its role and mechanism remain ambiguous due to the lack of comprehensive structural and functional studies on TSPAN1. Therefore, structural information is lacking as well. This study explored its intramolecular dynamics, stabilization, and potential ligand binding sites through the characterization of the three- dimensional structure of TSPAN1 using homology modeling and molecular dynamics simulations, compounded with network analysis, principal component analysis (PCA), and hydrogen bond analysis.